2006
DOI: 10.1016/j.cardfail.2006.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Adherence to the Sodium-Restricted Diet in Patients With Heart Failure

Abstract: Background-Despite the importance of the sodium restricted diet (SRD) to heart failure (HF) management, patient adherence is poor. Little is known about gender differences in adherence or factors that affect patients' ability to follow SRD recommendations. The purposes of this study were to determine whether there were gender differences in (1) adherence to the SRD; (2) knowledge about SRD and HF self-care; and (3) perceived barriers to following the SRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 41 publications
6
83
1
Order By: Relevance
“…Eleven of the articles were rated as good quality, fifteen as fair quality (the articles are numbered according to quality score in Tables 2 and 4; studies numbered 1-11 are rated as good quality [18][19][20][21][22][23][24][25][26][27][28], and those numbered 12-26 are rated as fair quality [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]). Four articles were excluded due to a low quality score [44][45][46][47]. Various HF self-care behavioral outcomes were reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven of the articles were rated as good quality, fifteen as fair quality (the articles are numbered according to quality score in Tables 2 and 4; studies numbered 1-11 are rated as good quality [18][19][20][21][22][23][24][25][26][27][28], and those numbered 12-26 are rated as fair quality [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]). Four articles were excluded due to a low quality score [44][45][46][47]. Various HF self-care behavioral outcomes were reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…18 Congruent with this observation, a recent study reported that only 34% of patients consume Ͻ3000 mg and only 15% consume Ͻ2000 mg sodium daily based on their 24-hour urinary sodium excretion. 20 Sodium consumption Ͻ2000 mg/d is difficult to achieve even with dietician education, 21 and studies have demonstrated that sex 22 and race 23 affect dietary preferences and adherence to sodium restriction recommendations in patients with HF.…”
Section: Sodium Intake Recommendations and Patternsmentioning
confidence: 99%
“…• Researchers suggest that lack of knowledge is a major barrier in diet adherence (Chung et al, 2006). Socioeconomic status…”
Section: A Concept Analysis: Adherence and Weight Lossmentioning
confidence: 99%
“…• Recommendations from healthcare providers to follow a sodium retracted diet is fundamental to patient adherence (Chung et al, 2006). Mental status stress level…”
Section: Antecedent Descriptionmentioning
confidence: 99%